2020
DOI: 10.7759/cureus.11720
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Obesity on Operative Time and Postoperative Complications for Peritrochanteric Femur Fractures

Abstract: Introduction The high prevalence of obesity among adults in the United States presents significant challenges to orthopedic surgeons. Obesity has been shown to increase operative time and complications in both elective and nonelective orthopedic surgeries. Despite this, there is a lack of literature evaluating the effect obesity has on operative time and postoperative complications following peritrochanteric fracture surgery. Methods and Materials We performed a retrospective review of patients who underwent i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…However, a contrasting perspective study from a femur fracture fixation study where, despite the association of obesity with prolonged operative durations, postoperative complications between obese and non-obese patients did not differ significantly. This included repeat surgeries and surgeries for infection up to 90 days postoperatively [ 3 ]. Those authors postulated that patient positioning, intraoperative imaging, and difficulties in fracture reduction demanded added surgical effort and time, contributing directly to the longer duration of surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a contrasting perspective study from a femur fracture fixation study where, despite the association of obesity with prolonged operative durations, postoperative complications between obese and non-obese patients did not differ significantly. This included repeat surgeries and surgeries for infection up to 90 days postoperatively [ 3 ]. Those authors postulated that patient positioning, intraoperative imaging, and difficulties in fracture reduction demanded added surgical effort and time, contributing directly to the longer duration of surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Since mortality rates are low in the setting of rib fracture surgeries, our present study examined only in-patient outcomes and did not address possible benefits associated with a higher BMI status. Meanwhile, other studies report that hip fracture surgeries in obese patients take significantly longer operative time and demand more work from surgeons compared to their non-obese counterparts [ 3 ], which ultimately leads to increased LOS and higher medical bills. In fact, among the various patient-related factors affecting surgical durations, a BMI exceeding 30 stands out as the most influential [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we found obesity to be associated with an increased mean operative time, a finding consistent with that of other orthopedic procedures including reverse TSA, peritrochanteric femur fractures, anterior cruciate ligament reconstructions, and distal radius fractures. 12 , 18 , 28 , 32 , 37 , 44 Compared to those with a normal BMI, obese patients required 132% more time to complete surgery. This may be indicative of difficulty with positioning obese patients, creating portals, as well as the potential need for special instruments.…”
Section: Discussionmentioning
confidence: 99%
“…Other orthopaedic realms such as arthroplasty, trauma, and spine have similarly seen prolonged operative times in this specific population. [21][22][23] In shoulder arthroscopy excess extremity fat theoretically complicates the surgery by limiting the identification of surface landmarks and causing soft tissue constraints leading to difficult maneuverability while facilitating the repair. Ultimately, this extended operative time prompts more resources, cost, and effort necessary to accomplish the same task.…”
Section: Discussionmentioning
confidence: 99%